(untitled) (Research, Society and Development, 2020)
The present work aims at analyzing the questions of Natural Sciences in the tests of the Exame Nacional do Ensino Médio (ENEM), regarding the competences and skills determined by the ENEM Reference Matrix (ENEM RM), and to evaluate the approach of Biology textbooks approved by the National Textbook Program (PNLD) 2018 under this same perspective. For that, the Biology’s questions of the ENEM tests of 2018 and 2019 were classified according to the theme and subtheme, and evaluated concernig the required competencies and skills. The three Biology textbooks of the PNLD 2018 most used in Brazilian public schools were analyzed as well. Ecology and Pollution were, respectively, the themes and subthemes most present in the analyzed tests. To solve the questions, different competencies and skills were required, with emphasis on the competence C3 and on the skills H10 and H12. In the analyzed textbooks, complementary materials on the themes, diverse visual resources and activities were highlighted. No multidisciplinary problems were found. The evaluated textbooks presented quite different approaches regarding the competences and abilities. In this way, it becomes evident that efforts are needed so that the High School may effectively offer to the students opportunities to develop competences and skills by means of interdisciplinary teaching, contextualized and focused on the solution of study cases applicable to their daily lives.